Speech Act Analysis on Statements Delivered by The Minister of Foreign Affairs of The Republic of Indonesia - Ahsan, Aidin; Fitrawati, Fitrawati (Universitas Negeri Padang, 2023)
This research investigates a speech act and felicity condition from the minister of foreign affairs of the Republic of Indonesia. In this research, the researcher analyzed speech act categories and felicity conditions in a statement. This research used descriptive qualitative research to analyze. The instrument of this research was the researcher himself. Transcripts and note-taking were also used to collect the data. The researcher analyzed three parts: the list and collection of all the statements, categories, types of speech acts, and felicity conditions. Lastly, conducted all types of speech acts and felicity condition types were found in the statement. As a result, the researcher found 70 assertive, 44 directive, 47 commissive, 12 expressive, and five declarative for illocutionary acts. Then, perlocutionary acts are 86 persuading, 80 convincing, and 12 scaring. And for the felicity condition shows 41 propositional content conditions, 61 preparatory conditions, 47 sincerity conditions, and 29 essential conditions. In conclusion, the minister's statement contains assertive and persuasive speech acts, so the condition of felicity is a condition of preparation. In addition, ministerial statements have followed the rules of Indonesia's free and active foreign policy.